School Surveillance in Context: High School Students' Perspectives on CCTV, Privacy, and Security. Issue 7 (October 2020) - Birnhack, Michael; Perry-Hazan, Lotem
This study examines high school students' perceptions of school closed-circuit television systems (CCTVs). It draws on interviews conducted with 83 adolescents recruited from 10th- to 12th-grade classes at 39 Israeli schools. The findings indicate that students' perceptions of CCTVs are embedded in their overall opinions about their school, particularly concerning relationships and trust between students and educators. The various metaphors that students used to describe their relational position regarding school CCTVs highlight that surveillance has become part of the organizational–educational experience. The findings also show that students' scrutiny of school CCTVs reflects a conflict between privacy and security concerns. Students resolve this conflict by resorting to various balances, which echo general constitutional principles but were also anchored in the students' personal schooling experiences. While building on Nissenbaum's framework of contextual integrity for assessing privacy violations, we challenge its assumption of a uniform set of informational norms within a given context.